Spore reproduction, glomalin content, and maize growth on mycorrhizal pot culture using acid mineral soil-based media - Vita Ratri Cahyani; Dianing Wahyu Kinasih; Purwanto Purwanto; Jauhari Syamsiyah (Universitas Sebelas Maret, 2022)
Arbuscular mycorrhiza (AM) is known as multifunctional fungi for plant helpers under adverse conditions. However, studies that focused on the production strategy of AM biofertilizers with specific targets related to the soil limitations are limited. This study aimed to examine AM inocula from several sources using various compositions of acid mineral soil-based media and maize hosts in pot cultures to obtain effective AM inocula to handle the phosphor (P) limitations in acid mineral soils. Zeolite and Inceptisols were used as comparing media. The study utilized a completely randomized factorial design with two factors, namely C = media composition (C0: zeolite; C1: representative media of Alfisols; C2: typical media of a mixture of Alfisols, Oxisols, and Ultisols; C3: typical media with the addition of Bio-RP nutrition; C4: Inceptisols) and I = AM inoculum source (I0: without inoculum; I1: inoculum from Alfisols; I2: mixed inoculum from Alfisols, Ultisols, and Oxisols; I3: mixed inoculum from eight soil types), and six replications per treatment combination. The AM cultures on acid mineral soil-based media, which yielded the highest mycorrhizal infection, spore reproduction, and glomalin content, were C1I2 and C3I2, while the highest maize growth and P concentration were obtained with C1I1, CII2, C2I1, and C3I2. Compared to all the treatments, C1I1 and C1I2 are the superior AM cultures. Further study is necessary to confirm the effectiveness of AM cultures.